Selective analysis of newly synthesized proteins by combining fluorescence correlation spectroscopy with bioorthogonal non-canonical amino acid tagging. Issue 2 (11th November 2020) - Yao, Jun; Huang, Xiangyi; Ren, Jicun
Abstract : FCS with the BONCAT strategy is a promising approach for analysis of newly synthesized proteins and also be extended to further application for studying physiological or pathological processes related to proteins or other metabolic molecular changes. Abstract : Protein expression is closely related to many biological processes including cell growth, differentiation and signaling. It is a challenge to selectively monitor newly synthesized proteins under both physiological and pathological conditions due to shortage of efficient analytical methods. Here, we proposed a new strategy to selectively monitor newly synthesized proteins in cells by combining fluorescence correlation spectroscopy (FCS) with bioorthogonal noncanonical amino acid tagging (BONCAT) technique. Firstly, homopropargylglycine (HPG), an alkyne surrogate of methionine, was metabolically incorporated into newly synthesized proteins in living cells, and the proteins containing the alkyne functional group were subsequently labeled with chemoselective fluorescence reporters using the Cu(i )-catalyzed azide–alkyne cycloaddition (CuAAC) reaction. Then, FCS was used to analyze the newly synthesized proteins based on the difference in the characteristic diffusion times of labeled proteins and free fluorescent dyes. We optimized the conditions of HPG metabolic incorporation and the CuAAC click reaction and applied this new method to study autophagic protein degradation and in situ monitor secreted proteins in cells. Compared to current methods, our method is simple, fast, and without separation, and it may become a promising approach for in situ studying protein expression in living cells.